ANALISIS PERBANDINGAN TRADING VOLUME ACTIVITY, ABNORMAL RETURN SAHAM DAN BID ASK SPREAD SEBELUM DAN SESUDAH STOCK SPLIT - Indria Octaviani; Ati Harianti (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2021)
A stock split is when a company divides the existing shares of its stock into multiple new shares. The split is done by dividing  each existing shares into more than one shares. A lower share price can make the stock more attractive to a broad range of investors so that the sale of shares can be further increased. This study aims to determine the differences in trading volume activity, abnormal returns and bid-ask spreads before and after the stock split. The event window used in this study is 20 days consisting of 10 days before the stock split and 10 days after the stock split. This study was conducted on 28 companies that announcess Stock Splits during the 2015-2019 period. The method used in this study was to use the Wilcoxon signed rank test which was processed with the help of SPSS version 25. The results of this study indicate that there are significant differences in Trading Volume Activity and Abnormal Return before and after the announcement of Stock Split